Efficacy and Safety of Levetiracetam in Refractory Seizures in Children - Zia ur Rehman, Nuzhat Noureen, Abdul Basit, Muhammad Yousaf (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess efficacy and safety of Levetiracetam (LEV) as add-on therapy in children with refractory seizure. Methodology: This prospective observational cohort study was conducted in the Outpatient Department of Paediatric Neurology, “The Children’s Hospital & Institute of Child Health, Multan”, Pakistan from 15th January 2020 to 14th January 2021. Fifty children of aged 2 months to 14 years of both genders with refractory epilepsy were enrolled and received oral LEV. Data on LEV efficacy and side effects were recorded. The medication was considered as “effective” when all seizures had ceased within 3 months, “partially effective” when seizure frequency was decreased by ≥50% and “ineffective” when seizure frequency was decreased by < 50%.or seizure frequency remain unchanged during a period of 3 month. Results: Out of a total of 50 participants, there were 35 (70.0%) male. Mean age was 4.81±3.79 years while mean age at onset of seizures was 2.51±2.85 years. Most frequent type of seizures was generalized tonic clonic seizures in 19 (38.0%) patients followed by focal clonic seizures in 13 (26.0%) patients. Levetiracetam was effective in 14 (28%) patients, partially effective in 24 (48.0%) and not effective in 12 (24.0%) patients. Conclusion: Levetiracetam as add-on therapy reduced the seizure frequency in 76% of the participants without any significant side effects. Keywords: Levetiracetam, refractory seizure, epilepsy, add-on therapy, efficacy.